Effects of ambient CO2 and H2O on soot processes in n-dodecane spray combustion using large eddy simulation. (15th March 2022) - Zhang, Min; Ong, Jiun Cai; Pang, Kar Mun; Bai, Xue-Song; Walther, Jens H.
Abstract: In this study, large eddy simulations, coupled a two-equation soot model, are performed to investigate the effects of ambient carbon dioxide (CO2 ) and water (H2 O) additions on the soot formation and oxidation processes in an n -dodecane spray flame. In the soot model, acetylene (C2 H2 ) is soot precursor and surface growth species, while hydroxyl radical (OH) and oxygen (O 2 ) are soot oxidizers. The effect of ambient CO2 and H2 O additions on soot formation/oxidation can be separated into thermal and chemical effects. For the thermal effects, the ambient CO2 and H2 O additions increase C2 H2 but reduce OH formation by lowering the flame temperature. This leads to a higher soot mass formed. On the contrary to the thermal effects, the ambient CO2 and H2 O additions reduce the soot formation due to their chemical effects. The reaction CH 2 ∗ + CO 2 ↔ CH 2 O + CO is found to be responsible for reducing C2 H2 formation. The ambient H2 O addition results in a higher OH but lower the C2 H2 mass formed owing to the reverse reactions H 2 + OH ↔ H 2 O + H and OH + OH ↔ H 2 O + O . Furthermore, the chemical effects is more significant than the thermal effects under the tested conditions. This leads to a lower soot mass formed when adding ambient CO 2 and H2 O. Highlights: Soot suppression effect due to ambient CO2 and H2 O additions is captured using LES. Thermal effects of CO2 and H2 O promote soot, but their chemical effects inhibit soot. The mechanisms of soot suppression due to ambient CO2 and H2 O additions are revealed.